2012
DOI: 10.1002/ajim.22127
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of epicondylitis, rotator cuff syndrome, and low back pain in latino poultry workers and manual laborers

Abstract: Epicondylitis, rotator cuff syndrome, and low back pain are common in immigrant Latino workers, and may negatively impact long-term health and contribute to occupational health disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 27 publications
1
22
1
Order By: Relevance
“…The proportion of those diagnosed with these musculoskeletal injuries was similar to the proportion to the total sample of participants in the larger study that included men as well as women [Cartwright et al, 2012;Rosenbaum et al, 2013]. The prevalence for epicondylitis and CTS were similar to that reported in the literature for other working populations.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The proportion of those diagnosed with these musculoskeletal injuries was similar to the proportion to the total sample of participants in the larger study that included men as well as women [Cartwright et al, 2012;Rosenbaum et al, 2013]. The prevalence for epicondylitis and CTS were similar to that reported in the literature for other working populations.…”
Section: Discussionsupporting
confidence: 79%
“…Data for this analysis are from a study comparing Latino poultry processing workers occupational injuries with those among other Latino manual workers [Arcury et al, 2012a;Cartwright et al, 2012;Pichardo-Geisinger et al, 2013;Rosenbaum et al, 2013]. Data were collected from 2009 to 2011.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, Schulz et al [5] describes that the back symptoms and wrist/ hand symptoms were reported by over 35% of Latino workers. In the same way, Rosenbaum et al [6] identiies that upper body musculoskeletal and low back pain are common in immigrant Latino workers and may negatively impact long-term health and contribute to occupational health disparities. Xiao et al [8] and Cartwright et al [9] describe the Latino population as a vulnerable group for MSDs.…”
Section: Resultsmentioning
confidence: 92%
“…MSDs have been extensively studied in several countries; however, few studies have been carried out so as to investigate the relationship between MSDs and ethnicity [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%